INTERNALIZATION OF POLITENESS VALUES FOR BUILDING QURANIC GENERATION - Sauri, Sofyan; Hamdani, Wagino Hamid; Sanusi, Anwar (Faculty of Language and Literature Education, Universitas Pendidikan Indonesia, 2020)
Changes in values often occurred in education are changes in the characters of generation of the nation, Indonesian students, who are far from the values of courtesy. Therefore, preventive and curative efforts are necessary to solve those problems, involving serving the community. Thus, this study was aimed at revealing the efforts to build the Qur’anic generation through internalizing politeness values in language use in light of the Qur’an perspective. Politeness principles in language use in the Qur’an were reflected in six phrases, namely; qaulan sadidan, ma’rufan, balighan, maysuran, layyinan, and kariman. The target of the activities in this study was Islamic forums, youth organizations, teachers, and parents. The results of this study indicated that the internalization of politeness values in language use in light of the Qur’an perspective was well and perfectly aligned, while the politeness values in language use in the perspective of the Qur'an practiced by the participants in their daily life were justice, honesty, gentleness, assertiveness, generosity, calmness, kindness, smooth, pleasant, polite and modesty.